Microbial Degradation of Aldrin and Dieldrin: Mechanisms and Biochemical Pathways - Pang, Shimei; Lin, Ziqiu; Li, Jiayi; Zhang, Yuming; Mishra, Sandhya; Bhatt, Pankaj; Chen, Shaohua (Frontiers in Microbiology, 2022)
As members of the organochlorine group of insecticides, aldrin and dieldrin are effective at protecting agriculture from insect pests. However, because of excessive use and a long half-life, they have contributed to the major pollution of the water/soil environments. Aldrin and dieldrin have been reported to be highly toxic to humans and other non-target organisms, and so their use has gradually been banned worldwide. Various methods have been tried to remove them from the environment, including xenon lamps, combustion, ion conversion, and microbial degradation. Microbial degradation is considered the most promising treatment method because of its advantages of economy, environmental protection, and convenience. To date, a few aldrin/dieldrin-degrading microorganisms have been isolated and identified, including Pseudomonas fluorescens, Trichoderma viride, Pleurotus ostreatus, Mucor racemosus, Burkholderia sp., Cupriavidus sp., Pseudonocardia sp., and a community of anaerobic microorganisms. Many aldrin/dieldrin resistance genes have been identified from insects and microorganisms, such as Rdl, bph, HCo-LGC-38, S2-RDLA302S, CSRDL1A, CSRDL2S, HaRdl-1, and HaRdl-2. Aldrin degradation includes three pathways: the oxidation pathway, the reduction pathway, and the hydroxylation pathway, with dieldrin as a major metabolite. Degradation of dieldrin includes four pathways: oxidation, reduction, hydroxylation, and hydrolysis, with 9-hydroxydieldrin and dihydroxydieldrin as major products. Many studies have investigated the toxicity and degradation of aldrin/dieldrin. However, few reviews have focused on the microbial degradation and biochemical mechanisms of aldrin/dieldrin. In this review paper, the microbial degradation and degradation mechanisms of aldrin/dieldrin are summarized in order to provide a theoretical and practical basis for the bioremediation of aldrin/dieldrin-polluted environment.